Exploring the Impact of a Low-Protein High-Carbohydrate Diet in Mature Broodstock of a Glucose-Intolerant Teleost, the Rainbow Trout - Callet, Thérèse; Hu, Huihua; Larroquet, Laurence; Surget, Anne; Liu, Jingwei; Plagnes-Juan, Elisabeth; Maunas, Patrick; Turonnet, Nicolas; Mennigen, Jan Alexander; Bobe, Julien; Burel, Christine; Corraze, Geneviève; et al. (Frontiers in Physiology, 2020)
Sustainable aquaculture production requires a greater reduction in the use of marine-derived ingredients, and one of the most promising solutions today is the augmentation in the proportion of digestible carbohydrates in aquafeed. This challenge is particularly difficult for high trophic level teleost fish as they are considered to be glucose-intolerant (growth delay and persistent postprandial hyperglycemia observed in juveniles fed a diet containing more than 20% of carbohydrates). It was previously suggested that broodstock could potentially use carbohydrates more efficiently than juveniles, probably due to important metabolic changes that occur during gametogenesis. To investigate this hypothesis, two-year old male and female rainbow trout (Oncorhynchus mykiss) were either fed a diet containing no carbohydrates (NC) or a 35%-carbohydrate diet (HC) for an entire reproductive cycle. Zootechnical parameters as well as the activities of enzymes involved in carbohydrate metabolism were measured in livers and gonads. Fish were then reproduced to investigate the effects of such a diet on reproductive performance. Broodstock consumed the HC diet, and in contrast to what is commonly observed in juveniles, they were able to grow normally and they did not display postprandial hyperglycaemia. The modulation of their hepatic metabolism, with an augmentation of the glycogenesis, the pentose phosphate pathway and a possible better regulation of gluconeogenesis, may explain their improved ability to use dietary carbohydrates. Although the HC diet did induce precocious maturation, the reproductive performance of fish was not affected, confirming that broodstock are able to reproduce when fed a low-protein high-carbohydrate diet. In conclusion, this exploratory work has shown that broodstock are able to use a diet containing digestible carbohydrates as high as 35% and can then grow and reproduce normally over an entire reproductive cycle for females and at least at the beginning of the cycle for males. These results are highly promising and suggest that dietary carbohydrates can at least partially replace proteins in broodstock aquafeed.